Impact of cardio-renal syndrome on adverse outcomes in patients with Fabry disease in a long-term follow-up. (15th December 2017) - Siegenthaler, M.; Huynh-Do, U.; Krayenbuehl, P.; Pollock, E.; Widmer, U.; Debaix, H.; Olinger, E.; Frank, M.; Namdar, M.; Ruschitzka, F.; Nowak, A.
Abstract: Aims: Fabry disease (FD) is a rare X-linked lysosomal storage disease with a deficiency of α-galactosidase A leading to progressive sphingolipid accumulation in different organs, among them heart and kidney. We evaluated the impact of cardio-renal syndrome (CRS) on the incidence of major cardiovascular complications and death in a prospective FD cohort. Methods and results: A total of 104 genetically proven FD patients were annually followed at the University Hospitals Zurich and Bern. The main outcome was a composite of incident renal replacement therapy (RRT), hospitalisation due to decompensated Heart Failure, new onset atrial fibrillation, pacemaker/ICD implantation, stroke/TIA and death. Estimated glomerular filtration rate (eGFR) and left ventricular myocardial mass index (LVMMI) where explored as the primary exposure variables. During the median follow-up of 103 [59–155] months, events occurred in 27 patients. In a Cox regression analysis, both higher LVMMI and lower eGFR were independently associated with a greater risk of developing adverse events after adjustment for multiple confounders (HR 1.67 [1.04–2.73] P = 0.03 per SD increase in LVMMI, HR 0.45 [0.25–0.83], P = 0.01 per SD decrease in eGFR). In patients with CRS, the risk to develop events was significantly increased if adjusted for demographics and RRT (HR 4.46 [1.07–18.62], P = 0.04), approaching significance if additionally adjusted for hypertension (HR 4.05 [0.95–17.29], P = 0.06). In Kaplan-Meier-Analysis, the poorest event-free survival was observed among patients with CRS. Conclusions: CRS was associated with a high risk to develop cardiovascular complications and death, emphasizing the importance of its prevention and early recognition. A focus on cardio-reno-protective therapies is crucial.